Standardization of the One-anastomosis Gastric Bypass Procedure for Morbid Obesity: Technical Aspects and Early Outcomes. Issue 2 (7th April 2023) - Sakran, Nasser; Haj, Bassel; Pouwels, Sjaak; Buchwald, Jane N.; Abo Foul, Salma; Parmar, Chetan; Awad, Ali; Arraf, Jabra; Omari, Abdallah; Hamoud, Mohamad
Abstract : Background: One-anastomosis gastric bypass (OAGB) has become an accepted metabolic/bariatric surgery procedure. This study aimed to describe our center's standardized OAGB operative technique and report early (≤30 d) safety outcomes in patients with severe obesity. Methods: The medical records of patients who had undergone either primary (n=681, 88.0%) or revisional OAGB (n=93, 12.0%) were retrospectively evaluated. Patient demographics, operative time, length of hospital stay, readmissions, reoperations, and ≤30-day morbidity and mortality rates were analyzed. Results: A total of 774 consecutive patients with severe obesity (647 female, 83.6%) underwent OAGB between January 2016 and December 2021. Their mean age was 36.2±10.8 years (range: 18 to 70 y) and mean body mass index was 42.7±4.2 kg/m 2 (range: 17.2 to 61 kg/m 2 ). Mean operating time was 52.6±19.9 minutes (range: 25 to 295 min) and length of hospital stay was 1.6±0.9 days (range: 1 to 9 d). Early postoperative complications occurred in 16 cases (2.1%), including 2 leaks with an intra-abdominal abscess (0.3%), bleeding (n=3, 0.4%), acute kidney failure (n=1, 0.15%), urinary tract infection (n=2, 0.3%), and intensive care unit stay (n=4, 0.5%). Seventy patients (9.1%) were readmitted, and re-laparoscopy was performed in 1 patient (0.1%). There was no mortality. Conclusions: In the very early term, OAGB was a safe primary and revisional metabolic/bariatric surgery operation. Consistent performance of a standardized OAGB procedure contributed to low rates of morbidity and mortality in the hands of metabolic/bariatric surgeons with good laparoscopic skills at a high-volume center.